Towards a unified framework for routing and scheduling planning in an integrated continuous care unit - Godinho, M. T.; Lopes, M. J. (Operations Research for Health Care in Red Zone: ORAHS 2022, Conference Proceedings, 2023)
We study a real world routing and scheduling problem arising in home health care context. Requisites defined by stakeholders are introduced and examined. Then, the problem is modeled as a Time-constrained Vehicle Routing Problem with Time Windows and a new Single Commodity Flow Formulation is proposed. Valid Inequalities to enhance the model are presented. Extensions of the problem, such as aggregating different types of care and of ensuring a threshold on the difference between the duration of the routes, are also discussed. We discuss the results obtained from a set of computational tests on instances adapted from the literature.